Exploring the Efficiency of Students’ Self-Made Reading Assessment Devices in Enhancing Reading Comprehension and Interest: A Classroom Action Research - Afriani, Masayu Neni; Sari, Artanti Puspita; Firdaus, Masagus (Journal of Social Work and Science Education, 2023)
This study investigates the effectiveness of a self-made reading assessment strategy in enhancing the reading comprehension skills and reading interest of eleventh-grade students at SMA Negeri 20 Palembang. The research follows an action research design, with two implementation cycles. In the first cycle, the strategy is integrated into reading instruction, and learning objectives are established. The second cycle focuses on implementing the strategy and guiding students in using self-made assessment tools. The results show a positive impact on students’ reading comprehension achievement, with a significant increase in the percentage of students meeting the passing grade from the first cycle to the second cycle. Additionally, the study reveals a noteworthy improvement in students’ reading interests. The implementation of the self-made reading assessment strategy enhances student engagement, motivation, and enthusiasm for reading. The use of self-made assessment tools encourages students to explore additional reading materials, leading to increased reading interest and knowledge acquisition. These findings contribute to the field of education by highlighting the effectiveness of the self-made reading assessment strategy in improving students’ reading abilities and fostering their interest in reading. The study emphasizes the importance of ongoing reflection and refinement in instructional approaches to sustain and enhance students’ reading skills.